2021
DOI: 10.3390/coatings11040414
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Layer Graphene Oxide in Human Keratinocytes: Time-Dependent Cytotoxicity, Proliferation, and Gene Expression

Abstract: Few-layer graphene oxide (GO) has shown no or very weak cytotoxicity and anti-proliferative effects in a wide range of cell lines, such as glioma cells and human skin HaCaT cells at concentrations up to 100 µg/mL. However, as multi-layer GO has hardly been explored in the biomedical field, in this study, this other type of GO was examined in human keratinocyte HaCaT cells treated with different concentrations, ranging from 0.01 to 150 µg/mL, for different periods of time (3, 12, and 24 h). The results revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…It can be activated by different substances, such as genoposidic acid [ 72 ], sinapic acid [ 73 ], or nicotinyl–isoleucine–valine–histidine [ 64 ]. However, other promising compounds such as graphene oxide, are not able to upregulate the SOD1 gene using non-cytotoxic concentrations [ 74 ]. In the present study, SOD1 was upregulated with extracellular Zn 2+ at the highest concentration (5 µg/mL), suggesting that non-cytotoxically extracellular Zn 2+ concentrations are able to induce an antioxidant effect in HaCaT keratocytes.…”
Section: Resultsmentioning
confidence: 99%
“…It can be activated by different substances, such as genoposidic acid [ 72 ], sinapic acid [ 73 ], or nicotinyl–isoleucine–valine–histidine [ 64 ]. However, other promising compounds such as graphene oxide, are not able to upregulate the SOD1 gene using non-cytotoxic concentrations [ 74 ]. In the present study, SOD1 was upregulated with extracellular Zn 2+ at the highest concentration (5 µg/mL), suggesting that non-cytotoxically extracellular Zn 2+ concentrations are able to induce an antioxidant effect in HaCaT keratocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Both nanocompounds showed a slightly statistically significant proliferative activity at 96 h of exposure time. A shorter exposure time (72 h) was not long enough to induce cell proliferation, as has been found for other nanomaterials such as GO [ 48 ]. CNFs at 10 μg/mL was not a high enough concentration to induce any proliferative effect.…”
Section: Discussionmentioning
confidence: 95%
“…The CNFs also increased the expression of the genes involved in the synthesis of glycoproteins such as cadherin 1 ( CDH1 ) and fibrillin ( FBN ), which are essential in the morphogenesis and development of normal tissue by connecting cells with each other [ 56 , 57 ]. The COL4A1 gene, which is abundant in the dermis, and the MMP1 gene, which is involved in the breakdown of the extracellular matrix in normal physiological processes, were also up-regulated after exposure of keratinocytes to CNFs for 24 h. The up-regulation of four of these eight genes ( FN1, TGFB1, CAT and CDH1 ) has also been observed in other CBNs such as multilayer GO [ 48 ]. However, the increase of the expression of the GPX1 gene was not observed in multilayer GO, probably due to the low non-cytotoxic concentration used (0.05 μg/mL) in that study because, as was found in the present study, this increase was only found at a much higher CNF concentration (40 μg/mL).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The GO affects cell proliferation, particularly osteogenic types [ 277 ], but has not shown toxic properties [ 288 ]. According to Salesa et al [ 289 ] is essential to notice that toxicological differences between single-layer GO and multilayer GO may be observed and represent an important aspect.…”
Section: Reviewmentioning
confidence: 99%